Correlation between organizational learning and employee productivity in the gulf cooperation council - Salim Marhoon Salim Al Mamari, Mohammed Abdul Imran Khan, (Opción, 2019)
This article attempts to examine the relationship between organizational learning and organizational learning in the Gulf Cooperation Council. The study was conducted through an empirical research design; a survey method was employed and the study population comprised 15 banks in Oman. The research believes that the result of this study may be inferred to all GCC member countries. The researchers find that there is a strong, statistically significant positive relationship between organizational learning and organizational performance. In conclusion, organizations that invest in organizational learning reported improved employee productivity in Omani Banking Industry